Effects of endurance training on transient oxygen uptake responses in cyclists - Norris, S. R.; Petersen, S. R. (Journal of Sports Sciences, 1998)
The aim of this study was to determine the alterations in oxygen uptake kinetics following endurance training in previously trained athletes. Sixteen competitive cyclists completed 8 weeks of supervised endurance cycle training. Ventilatory threshold, maximal oxygen uptake (VO2max), oxygen uptake kinetics and simulated 40-km time-trial tests were performed three times over a 4-week period before training, and then after 4 and 8 weeks of training. The protocol for measuring oxygen uptake kinetics consisted of three square-wave increments from unloaded cycling to a power output of 78 W followed by a single increment from 78 to 156 W. No significant differences in any variables were observed over the pre-training period. The ventilatory threshold and VO2max increased, and the time for 40 km decreased (P < 0.05) with training. Shorter VO2 time constants and lower heart rates were observed during the protocol for measuring oxygen uptake kinetics (same absolute power output) post-training. These results indicate that oxygen uptake kinetics may be improved with endurance training in previously trained athletes. J Sports Sci 1998 Nov;16(8):733-8